Spontaneous Recovery of Paraplegia in a Polytrauma Patient following Spinal Cord Ischemia due to Type B Traumatic Aortic Dissection - Pedro Ramos Jurado; Fernando Hernández Aragón; Víctor Aaron Miranda González; Jesús Antonio Loya Silva; Edgar Azael Pérez Gutiérrez; Nadia Karina Portillo Ortiz; Adriana Cristina Quintana Vázquez; Luisa Fernanda Trujillo Venzor; Eduardo Enrique Gámez Aponte; Arturo Aguirre Madrid; Edmundo Berumen Nafarrate (Case Reports in Orthopedics)
Aortic dissection is a life-threatening acute condition characterized by the separation of the aortic wall’s layers. It is caused by a tear in the internal vascular wall (intimal layer and middle layer), which results in bleeding between the layers and causes abrupt and excruciating pain. The appropriate consideration must be given to the condition’s dynamic nature, and variations in clinical presentation, without neglecting the urgency for intervention. In this case study, a 65-year-old male engaged in a car accident is admitted to urgent care with a traumatic aortic dissection diagnosis that included the aortic arch, a segmental exposed fracture of 1/3 distal of the right femur AO 32C3k, and an intertrochanteric fracture AO 31A1.3. The patient developed transient paraplegia as the initial manifestation of acute aortic dissection, which represents a high mortality and morbidity entity without adequate and prompt treatment, and prompt diagnosis and management were critical. A patient with severe thoracic and abdominal trauma caused by high-energy injury should be properly evaluated for the possibility of traumatic aortic dissection. The endovascular aortic repair was performed, resulting in a positive clinical evolution due to the important participation of the multidisciplinary trauma team involved in patient management and prompted decision-making.